Building information modeling: implementation challenges in the Malawian construction industry - Ndwandwe, Melusi; Kuotcha, Witness; Mkandawire, Theresa (Frontiers in Built Environment, 2024)
Building information modelling is making waves in the global built environment, improving the architecture engineering and construction industry in many aspects. However, in Malawi, it is neither widely adopted nor well-researched. Therefore, this study aimed to identify and analyse the challenges of BIM implementation in Malawi. A quantitative methodology was used, collecting 189 questionnaires. Descriptive analysis (mean item score), one-sample t-test, and factor analysis were used to analyse the data. The descriptive analysis revealed differences in ranking the 20 BIM challenge factors among various groups, yet no statistically significant variances were found among them; all the challenges were deemed critical. However, the results of the one-sample t-test indicated statistically significant differences in 13 of the 20 challenges, including issues with expertise, experience, integrating multiple software, understanding BIM potential, implementation methods, change adaptation, legislative guidelines, high implementation costs, awareness, integration to traditional techniques, procurement procedures, and strategic vision for implementation. Thus, through factor analysis, the study divided the 20 BIM implementation challenges into three categories: BIM integration, collaborative workflow, and technical adaptability challenges. These findings would increase BIM awareness, best practices and solutions, collaboration and communication, training and education, and industry BIM adoption. The study further contributes to the body of knowledge by providing structured challenges for BIM implementation, filling the knowledge gap about BIM challenges in the Malawian construction industry.